TENDENCY TO COSMOPOLITANISM IN MODERN MORAL EDUCATION - J. SH. Mustafayev; I.E.Mardanov (Лучшие интеллектуальные исследования, 2024)
Annotation: This article highlights the characteristics of national moral education in the life of our society, the types of values, the role of values in human life.